2016
DOI: 10.4184/asj.2016.10.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Radiological Results of Posterolateral Fusion and Posterior Lumbar Interbody Fusion in the Treatment of L4 Degenerative Lumbar Spondylolisthesis

Abstract: Study DesignMulticenter analysis of two groups of patients surgically treated for degenerative L4 unstable spondylolisthesis.PurposeTo compare the clinical and radiographic outcomes of posterolateral fusion (PLF) and posterior lumbar interbody fusion (PLIF) for degenerative L4 unstable spondylolisthesis.Overview of LiteratureSurgery for lumbar degenerative spondylolisthesis is widely performed. However, few reports have compared the outcome of PLF to that of PLIF for degenerative L4 unstable spondylolisthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Furthermore, spinal fusion may prevent recurrent stenosis. Some studies have reported the same fusion rate in PLF and PLIF groups (50). Similarly to the findings of most studies (50) who reported that fusion rate in the PLIF is more than PLF, we found higher fusion rates in patients who underwent PLIF rather than PLF with posterior instrumentation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, spinal fusion may prevent recurrent stenosis. Some studies have reported the same fusion rate in PLF and PLIF groups (50). Similarly to the findings of most studies (50) who reported that fusion rate in the PLIF is more than PLF, we found higher fusion rates in patients who underwent PLIF rather than PLF with posterior instrumentation.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our findings, some authors have reported that the clinical results of PLIF are not superior than PLF in the treatment of lowgrade spondylolisthesis (14,41,48,58), although PLIF is expected to achieve better maintenance of correction and bony union. In addition, Kuraishi et al (50) reported that lumbar lordosis in the PLIF group was not better than that in the PLF group, which might be due to the lack of difference in clinical outcomes between the 2 groups.…”
Section: Discussionmentioning
confidence: 97%
“…Although lumbar interbody fusion techniques might yields higher fusion rates, still the clinical outcome with PLF is not compromised. 2,21,32 In the studied patients, the reduction of the mean VAS for back pain after six months postoperatively was 5.9±0.2. This is comparable to similar improvement in other instrumented PLF or PLIF/ TLIF/ALIF series, 3,2,4,32 with mean VAS reduction of 4.8±1.2, 5.2±1.1, 3.6±0.9, and 4.4±1.2 respectively.…”
Section: Discussionmentioning
confidence: 84%
“…However, operative time and EBL were greater in the PLF population. Two additional smaller recent retrospective studies also demonstrate no difference in clinical outcomes at long-term follow-up between PLF and either TLIF or PLIF [34,35].…”
Section: Interbody Fusionmentioning
confidence: 91%